Feasibility Analysis of Ecotourism in Nagari Sungai Pinang, Koto XI Tarusan sub-district, Pesisir Selatan Regency - Fransiska, Nia; Dasrizal, Dasrizal; Despica, Rika (Universitas Lambung Mangkurat, 2024)
This study aims to determine the physical condition of ecotourism and analyze the feasibility of tourist objects in Nagari Sungai Pinang as seen from the attractiveness criteria, accessibility, accommodation, and infrastructure. This type of research is descriptive. The research population is all tourist objects in Nagari Sungai Pinang, amounting to 12. The research sample was taken by purposive sampling from 4 beach tourism objects and one island tourism object that had been developed. Data collection used a questionnaire, data analysis was descriptive analysis with an evaluative approach, and the feasibility test was carried out through scoring calculations by the ODTWA guidelines. The results of the study found that: 1) The physical condition of the area of all tourist objects has a geographic location with proximity between objects one tourist object and another tourist object so that it has advantages in terms of accessibility, the state of the field with flat and mountainous relief becomes a high attraction, the condition of the soil and natural phenomena such as cliffs add to the aesthetics of the tourist attraction and moderate weather/climate conditions can support tourist activities. 2) comparing the feasibility index values of tour managers and visitors shows three feasible tourist objects to develop, namely Majunto Beach, Eco Beach, and Dhina Cheker Beach. In contrast, the tourist attractions of Marapalam Beach and Pamutusan Island are not yet feasible to develop.